2020
DOI: 10.3390/biomedicines8100377
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Neutralization of In Vitro Toxicity of Chinese Cobra (Naja atra) Venom by Different Antivenoms

Abstract: The Chinese Cobra (Naja atra) is an elapid snake of major medical importance in southern China. We describe the in vitro neurotoxic, myotoxic, and cytotoxic effects of N. atra venom, as well as examining the efficacy of three Chinese monovalent antivenoms (N. atra antivenom, Gloydius brevicaudus antivenom and Deinagkistrodon acutus antivenom) and an Australian polyvalent snake antivenom. In the chick biventer cervicis nerve-muscle preparation, N. atra venom (1–10 µg/mL) abolished indirect twitches in a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Therefore, it seems as though both antivenoms recognize the post- and pre-synaptic neurotoxins found in B. multicinctus venom. This is not surprising as we have previously shown cross neutralization between Australian polyvalent snake antivenom and non-Australian snake species including the Chinese cobra, New Guinea small-eyed snake, monocled cobra, banded krait, common krait and king cobra [ 16 , 17 , 18 ]. The ability of other heterologous antivenoms to neutralize the neuromuscular effects of Bungarus genus venoms and toxins has also been reported previously [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Therefore, it seems as though both antivenoms recognize the post- and pre-synaptic neurotoxins found in B. multicinctus venom. This is not surprising as we have previously shown cross neutralization between Australian polyvalent snake antivenom and non-Australian snake species including the Chinese cobra, New Guinea small-eyed snake, monocled cobra, banded krait, common krait and king cobra [ 16 , 17 , 18 ]. The ability of other heterologous antivenoms to neutralize the neuromuscular effects of Bungarus genus venoms and toxins has also been reported previously [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 78%
“…As previously described by us [ 15 , 16 , 18 ], male chickens (aged 4–10 days) were euthanized by exsanguination following CO 2 inhalation. Biventer cervicis nerve-muscle preparations were dissected and then mounted on wire tissue holders under 1 g resting tension in 5 mL organ baths.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used drugs are chymotrypsin and pancreatic enzymes. It is important to note that patients bitten by Chinese cobra must use the corresponding anti-snake venom, not geographically diverse snake anti-snake venoms since antigenicities of anti-snake venoms have been found to vary from one species to another, whose titer may be very low or even ineffective [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, cutting-edge nanofractionation analytics are employed to determine the effects of Varespladib and other small molecules on the coagulopathic effects of various crotalid and viperid snake venoms [ 61 , 62 ]. The Hodgson lab examined the neutralising abilities of different antivenoms against the effects of venom from the Chinese cobra by using the chick biventer nerve muscle preparation [ 63 ]. Another study on Australian snake venoms by Isbister et al found that phospholipase A2 levels in human snakebite victims could be used as an early indicator of envenomation by Australian elapids (with exception of brown snakes) [ 64 ].…”
Section: Contributions To This Special Issuementioning
confidence: 99%